Summative Test Items Analysis Using Classical Test Theory (CTT)/ Analisis Item Kertas Peperiksaan Sumatif Menggunakan Teori Ujian Klasik (TUK) (Sains Humanika, 2020)
Item analysis is the process of examining student responses to test items individually in order to get clear picture on the quality of the item and the overall test. Teachers are encouraged to perform item analysis for each administered test in order to determine which items should be retained, modified, or discarded in the given test. This study aims to analyse items in 2 summative examination question papers by using classical test theory (CTT). The instruments used were the SPM Mathematics Trial Examination Questions 1 2019 which involved 50 students in form 5 students and the SPM Mathematics Trial Examination Question 1 2019 which involved 20 students. The SPM Mathematics Trial Examination Question paper 1 contains 40 objective questions while the SPM Mathematics Trial Examination paper 1 contains 25 subjective questions. The data obtained were analysed using Microsoft Excel software based on the formulas of item difficulty index and discrimination index. This analysis can help teachers for better understanding about the difficulty level of the items used. Finally, based on the analysis items obtained, the items were classified as good, good but improved, marginal or weak items.
Keywords: Item analysis; Classical Test Theory; index difficulty; index discrimination; summative test